PENGEMBANGAN MEDIA INTERAKTIF BERBASIS DIGITAL UNTUK MENINGKATKAN MOTORIK KASAR ANAK USIA DINI DI TAMAN KANAK-KANAK KECAMATAN MARISA - Ria Ekawaty A. Mohamad; Misran Rahman; Muhammad Zubaedi (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to develop and implement digital-based interactive media that can improve the gross motor skills of early childhood in Marisa District Kindergarten. The method used is Research and Development (R&D) with a mix-method approach, which is a combination of qualitative and quantitative approaches. The research stages include needs analysis, media design, validation by experts, limited trials, and field trials. The research subjects consisted of teachers and kindergarten children involved in the media implementation process. The results of the study show that the interactive media developed is very feasible to use, based on the validation of media and PAUD experts with a feasibility score of more than 85%. Field trials showed a significant improvement in children's gross motor skills, from pretest results to posttest, with a significance value (p) < 0.05. Qualitatively, children look more active, enthusiastic, and motivated during the learning process. This media also received a positive response from teachers because it was easy to use and able to create an interesting learning atmosphere. In conclusion, this digital interactive media is effective in improving early childhood gross motor and can be used as an innovative alternative in technology-based learning in early childhood education.